Conceptual bases for reforming the national health care system: to the formulation of principles - H. S. Stetsenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2020)
The article is devoted to the problems of reforming domestic health care. First of all, what is worth paying attention to is the formulation of principles. Principles for public administration in the field of public health.